Navigating gender and sexuality in the classroom: Narrative insights from students and educators - McEntarfer, Heather Killelea (Routledge, 2016)
Gender identity and sexuality play crucial roles in the educational experiences of students, parents, and teachers. Teacher education must more directly address the ways that schools reflect and reproduce oppressive gender norms, working to combat homophobia, transphobia, heteronormativity, and gendered expectations in schools. This volume examines teacher candidates’ experiences with gender and sexuality in the classroom, offering insight and strategies to better prepare teachers and teacher educators to support LGBTQ youth and families. This volume addresses the need for broader, more in-depth qualitative data describing teacher candidates’ responses to diversity in the classroom (including gender, sexuality, race, class and religion). By using pedagogical tools such as narrative writing and positioning theory, teacher candidates explore these issues to better understand their own students’ narratives in deeply embodied ways. This book calls for schools to be places where oppression, in all its complexity, is explored and challenged rather than replicated.
Keywords: LGBTQIA2+; approches et analyses; discipline; formations; hétérosexisme; identités LGBTQIA2+; intersectionnalité; outils; outils didactiques; privilèges; pédagogie; religion; sciences de l'éducation; sexualité; systèmes d'oppressions; thématiques

Project Implicit
Test de préjugés inconscients
Keywords: approches et analyses; biais inconscients; cours; discipline; discours dominant; formations; inégalités; outils; pol5480; premier cycle; privilèges; psychologie; pédagogie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences